2010
DOI: 10.1590/s0100-06832010000500001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of litter layer removal on the soil thermal regime of a pine forest in a mediterranean climate

Abstract: SUMMARYThe removal of the litter layer in Portuguese pine forests would reduce fire hazard, but on the other hand this practice would influence the thermal regime of the soil, hence affecting soil biological activity, litter decomposition and nutrient dynamics. Temperature profiles of a sandy soil (Haplic Podzol) under a pine forest were measured with thermocouples at depths to 16 cm, with and without litter layer. The litter layer acted as a thermal insulator, reducing the amplitude of the periodic temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…; Andrade et al. ). Litter depth was estimated for each sampling point as the mean of three metric tape measurements.…”
Section: Methodsmentioning
confidence: 99%
“…; Andrade et al. ). Litter depth was estimated for each sampling point as the mean of three metric tape measurements.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Sakaguchi and Zeng (2009) implemented a specific resistance due to litter for soil evaporation. The inclusion of litter-related processes has been shown to have a substantial impact on hydrological (Putuhena and Cordery, 1996;Guevara-Escobar et al, 2007) and thermal processes (Andrade et al, 2010). Litter has an important insulating capacity as its thermal diffusivity is small compared to soil (Riha et al, 1980), which leads to a strong impact on the soil temperature diurnal cycle and ground conduction flux.…”
mentioning
confidence: 99%
“…Both effects alter soil conditions. Although we did not directly measure the soil conditions, previous studies (Andrade et al 2010;Cirtain et al 2009;Deutsch et al 2010) suggested those effects could elevate and maintain soil temperature and moisture. These microclimatic changes could facilitate the emergence of new shoots (Liu et al 2009;Wang and Kao 1986), thus promoting asexual reproduction in Yushan canes.…”
Section: Discussionmentioning
confidence: 99%